Hepatitis C prevalence in HIV infected heterosexual men and men who have sex with men - Gogela, Neliswa Antonia (Division of Hepatology, 2019)
Background: Globally 1% of individuals are infected with hepatitis C virus (HCV). In South Africa (SA), the prevalence ranges between 0.3% - 1% with few prospective screening data available. Similarly, local data on transmission modes of HCV are limited but probably include parenteral routes and pre-1992 blood or blood product products. The risk of heterosexually transmission is low but is increased in men who have sex with men (MSM) with co- transmission risk of both HIV and HCV. Objectives: Given a limited local understanding, we sought to better understand HCV characteristics and prevalence in 2 groups of HIV-infected men. Methods: HIV positive men in the greater Cape Town metropolitan area were recruited. Sexual orientation was self-identified and demographic and other personal data obtained via a confidentially administered questionnaire. Participants were screened for HCV after a blood draw and positive HCV Ab tests were tested for HCV RNA. Risk factors associated with HCV seropositivity were determined. Results: Five hundred HIV positive men were recruited; 215 (43%) non-MSM and 285 (57%) MSM, with median age 36 years (IQR 20 – 64) and 37 years (IQR 21 – 56), in the MSM and non-MSM group, respectively, p = NS. Overall, 3.4% (n=17) screened HCV positive, 5.6% (n=16) MSM and 0.5% (n=1) non-MSM, with 82.4% viremic for HCV RNA. In respect to genotype (GT) distribution, 50% were infected with GT1, 14.3% GT4 and 35.7% were GT2. In terms of risk, MSM were more likely to have used drugs (54.4% vs. 30.2%, p<0.001) and to have used all five modes of drugs administration (13% of MSM vs. 0.5% of non- MSM for injected drugs, 36.1% vs. 2.3% inhaled, 10% vs. 0% for the rectal route, 48.1% vs. 28.8% for smoked and 27.4% vs. 2.3% for oral drugs). More MSM than non-MSM (46.3% vs. 16.7%) reported sex whilst using recreational drugs and similarly more MSM (21.4% vs. 14%) reported having sex with a sex worker (SW).Risk factors for HCV seropositivity included drug use history (odds ratio (OR) 6.28, 98% confidence interval (CI). 1.78 – 22.12: p=0.004) and in MSM, sex with SW (OR 5.5, 95% 2.06 – 14.68; p=0.001) or use of recreational drugs with sex (OR 6.88, 95% CI 2.21 -21.44; p=0.001). Conclusion: HCV prevalence in HIV positive MSM is higher than previously appreciated or documented in South Africa. Risk factors include injecting drug use, use of recreational drugs with sex and sex with SWs. Targeted interventions are required to address this emerging challenge to achieve the viral hepatitis elimination ideal by 2030.